Zakonska ureditev financiranja javnih regulatornih agencij v luči ustavnih izhodišč - Triller Vrtovec, Katja (Pravnik, 2017)
In the manuscript the author summarizes the constitutional principles of public financing and the regulatory framework for financing of public regulatory agencies. On a case study of financing the Agency for Medicinal Products and Medicinal Devices of the Republic of Slovenia (JAZMP) the author tries to establish whether or not the compliance with the constitutional principle of legality in prescribing taxes influences the efficiency and cost-effectiveness of public regulatory agencies performance. In the assessment she uses three criteria: first, does the law prescribe the criteria for setting the JAZMP fees, second, does the law prescribe the JAZMP services financed by fees, and third, does the law prescribe the supervision over JAZMP prescription of fees.
Keywords: Agency for Medicinal Products and Medicinal Devices of the Republic of Slovenia; fees; financing of public regulatory agencies; financiranje javnih agencij; Javna agencija za zdravila in medicinske pripomočke; načelo financiranja državnih nalog z obveznimi javnimi dajatvami; načelo uravnoteženega proračunskega financiranja javne porabe; načelo zakonitosti pri predpisovanju obveznih dajatev; namenske javne dajatve; principle of balanced budgetary financing of public expenditures; principle of financing state duties with taxes; principle of legality in prescribing taxes; pristojbine; tarife; tariffs; taxes; upravne takse